2020
DOI: 10.1016/j.jad.2019.11.002
|View full text |Cite
|
Sign up to set email alerts
|

One-Year follow-up effects of a cognitive behavior therapy-based transdiagnostic program for emotional problems in young children: A school-based cluster-randomized controlled trial

Abstract: Background: The present study examined the long-term efficacy of a transdiagnostic prevention program, Super Skills for Life (SSL), among young children with emotional problems. SSL is based on the principles of cognitive behavioral therapy, behavioral activation, and social skills training.Methods: One-hundred twenty-three Spanish-speaking children, aged 6 to 8 years, and their parents participated in the study. They were recruited from ten schools. Schools were randomly allocated to either the intervention (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 37 publications
8
15
0
1
Order By: Relevance
“…Most of these positive effects were associated with large and very large effect sizes, which is consistent with results of the UP-A reported by Ehrenreich-May's group [12,13,15], as well as with findings of our group related to the Spanish version of the UP-A [16,17]. These data are also consistent with the results reported by authors who administered Super Skills for Life, a T-CBT protocol that has been applied as an indicated prevention program for adolescents [51] and children [52] at risk of developing anxiety disorders.…”
Section: Discussionsupporting
confidence: 92%
“…Most of these positive effects were associated with large and very large effect sizes, which is consistent with results of the UP-A reported by Ehrenreich-May's group [12,13,15], as well as with findings of our group related to the Spanish version of the UP-A [16,17]. These data are also consistent with the results reported by authors who administered Super Skills for Life, a T-CBT protocol that has been applied as an indicated prevention program for adolescents [51] and children [52] at risk of developing anxiety disorders.…”
Section: Discussionsupporting
confidence: 92%
“…The findings could be summarised as follows: first, as hypothesized and in line with previous studies Fernández-Martínez et al, 2020;Orgilés et al, 2020;Ramdhonee-Dowlot et al, 2021), total internalizing problems were significantly reduced from pre-test to follow-up assessments. Within the internalizing problems, significant reductions were found for somatic complaints, withdrawn and anxious/depressed subscales.…”
Section: Discussionsupporting
confidence: 84%
“…Recent studies have shown that the SSL is effective in reducing emotional problems such as anxiety and depressive symptoms as well as other forms of difficulties such as anxiety-related interferences, and peer and conduct problems among children and adolescents in school settings Fernández-Martínez et al, 2020;Orgilés et al, 2020) and in residential care institutions (Ramdhonee-Dowlot et al, 2021). However, studies that examined the role of gender, age, and school type in moderating the intervention outcome is lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, transdiagnostic treatment methodologies, which are more cost-effective and increase accessibility (Barlow & Farchione, 2017), have become increasingly popular with school-aged youth due to rapidly changing developmental profiles and comorbidity (Chu et al, 2016). It has also been found to be effective with social skills treatment (Fernández-Martínez et al, 2020;Gale, 2011). While transdiagnostic treatment strategies have been shown to be effective for supporting youth, accessibility to in-person interventions is limited.…”
mentioning
confidence: 99%